2012
DOI: 10.1186/1743-8977-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cellular uptake of genotoxic silica nanoparticles

Abstract: Mechanisms for cellular uptake of nanoparticles have important implications for nanoparticulate drug delivery and toxicity. We have explored the mechanism of uptake of amorphous silica nanoparticles of 14 nm diameter, which agglomerate in culture medium to hydrodynamic diameters around 500 nm. In HT29, HaCat and A549 cells, cytotoxicity was observed at nanoparticle concentrations ≥ 1 μg/ml, but DNA damage was evident at 0.1 μg/ml and above. Transmission electron microscopy (TEM) combined with energy-dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 57 publications
(77 reference statements)
4
105
0
Order By: Relevance
“…The enhanced aqueous solubility of curcumin in the HNT-Cur prodrug as well as the accelerated curcumin release from the nanoparticle triggered by intracellular GSH are responsible for the increased cytotoxicity of the HNT-Cur compared to free curcumin. Literature reports that particles ranging between 500 to 600 nm could cause either greater disruption [54] of the membrane or induced strong local membrane deformations, followed by internalization of the particles [55]. Although the large hydrodynamic radius measured for HNTCur, the actual size of the prodrug, as determined by SEM (Fig.…”
Section: Antiproliferative Activitymentioning
confidence: 90%
“…The enhanced aqueous solubility of curcumin in the HNT-Cur prodrug as well as the accelerated curcumin release from the nanoparticle triggered by intracellular GSH are responsible for the increased cytotoxicity of the HNT-Cur compared to free curcumin. Literature reports that particles ranging between 500 to 600 nm could cause either greater disruption [54] of the membrane or induced strong local membrane deformations, followed by internalization of the particles [55]. Although the large hydrodynamic radius measured for HNTCur, the actual size of the prodrug, as determined by SEM (Fig.…”
Section: Antiproliferative Activitymentioning
confidence: 90%
“…It should be noted that, to our knowledge, the only previous study on silica nanospheres with the conventional format of the liposome leakage assay as employed in the present work, reported that small, 14 nm diameter, nonfunctionalized silica particles at a very high particle concentration of 100 mg mL À1 (B45 nM) only induced B5-20% dye release from 400 nm liposomes (B15 pM concentration) of POPC/DOPE/DOPS/ cholesterol. 71 However, an initial increase in fluorescence signal was followed by a substantial intensity decrease, 71 indicative of photobleaching. Various other recent studies with biomembrane model systems, outlined below, have established that silica nanospheres are indeed able to perturb, by surface association, the structure of a lipid bilayer or monolayer, and that the extent of perturbation depends, also for particles o200 nm in diameter, on nanosphere size.…”
Section: à2mentioning
confidence: 99%
“…Data on the genotoxic properties of SAS, mostly assessed by the comet assay for detecting DNA damage or by the micronucleus assay for chromosomal damage, are however less clear. Generally, positive responses in genotoxicity assays are reported more frequently in vitro [5][6][7][8][9] than in vivo [10][11][12]. However, in vitro results remain quite variable and depend on the physical and chemical characteristics of the SAS and the cell type used.…”
Section: Introductionmentioning
confidence: 99%